Understanding Indigenous Learners’ Experiences During the First and Second Wave of the COVID-19 Pandemic - Auger, Josie C.; Baker, Janelle M.; Connors, Martin; Martin, Barbara (International Review of Research in Open and Distributed Learning, 2023)
This paper focuses on the experiences of Indigenous learners at Athabasca University. Having access to online education provided a sense of normalcy for students during the global pandemic while many post-secondary institutions and Indigenous communities were closed. The purpose of the research was two-fold: a) to determine the dynamics of reaching Indigenous learners and measuring their adaptability in learning during the COVID-19 pandemic, and b) to understand the effects of the pandemic on the mind, body, spirit, and social environment of Indigenous distance education learners and their families. This research included qualitative and quantitative methods, specifically, a survey, focus group, and individual interviews. We share the results of online research involving Indigenous students during the first and second waves of the COVID-19 pandemic. We concluded that listening to Indigenous students supported their online education while giving them an outlet to express their experiences. This research identified Indigenous student adaptations towards their spirituality in specific ways inherent to their culture given the reactions to COVID-19, their responses, and reflections.